Usury from an Islamic and historical perspective / Balqis Mohd Ramli … [et al.] - Mohd Ramli, Balqis; Mohd Yusoff, Nur Aisyah Atiqah; Mohd Rosly, Nuurul Farihah; Wan Ramli, Wan Nurain Afiqah (2023)
Title: "Usury from an Islamic and Historical Perspective"